Assessment of Sodium Content of Processed Food Available in Indonesia - Istiqomah, Nurani; Astawan, Made; Palupi, Nurheni Sri (Jurnal Gizi dan Pangan, 2021)
This study was conducted to identify the sodium content in processed food and determine the proportion of products that meet the World Health Organization (WHO) global sodium benchmark criteria. Spesific concern was placed for sodium content in instant noodles. A comparative analysis was conducted to determine the relevance between the WHO and Indonesian Food and Drug Authority (Indonesian FDA) benchmarks in limiting sodium in instant noodles. Data on sodium levels (mg/100 g) of processed food was obtained from the register in the Indonesian FDA, Directorate of Processed Food Registration for 2019 to 2020. There were 3,850 products, consisting of 3,036 Local Products (LP) and 814 Imported Products (IP). These products were grouped into seven food categories and 18 types of food. The highest sodium content was found in chili sauce at 2,254,06 mg/100 g, and the lowest was in wafers at 218.64 mg/100 g. Overall, 2,538 of all products (66.56%) did not meet the sodium criteria based on the WHO benchmark. While for instant noodles, only 14.2% of the products met the sodium criteria based on the Indonesian FDA regulations and only 7.4% comply to the WHO sodium benchmark. The Cohen’s Kappa test showed a strong agreement (K=0.650; 95% CI; p=0.00, strong) between the two regulations in limiting sodium levels in instant noodles. This study provides an overview of sodium levels in processed food in Indonesia. The sodium content in most products including instant noodles, as one of the most frequently consumed products, are still above the recommended value. Therefore, it is necessary to develop sodium benchmarkof wider range of food categories in national level that might contribute to sodium intake, as well as for instant noodles. In order to achieve this goal, involvement of multi stakeholder among government, food industry and expert are also needed to deliver effective policies regarding sodium intake concerns.